Association between dietary fiber intake and peripheral artery disease in hypertensive patients - Yingnan Liu; Ruihong Wei; Zhouyong Tan; Gaoyang Chen; Tao Xu; Zhaokang Liu; Hongtao Xiong; Chao Chen; Yongqing Zhuang (BMC, 2024)
Abstract Background At present, no studies explored whether dietary fiber intake was associated with the risk of peripheral artery disease (PAD) in hypertensive patients. This study assessed the association between dietary fiber intake and PAD in hypertensive patients. Methods This cross-sectional study collected the data of 4628 participants with the measurement of ankle-brachial pressure index in the National Health and Nutrition Examination Surveys database. Univariate logistic regression analysis was applied to identify variables associated with PAD as confounding factors. Univariate and multivariable logistic regression analyses were used to explore the association between dietary fiber intake and PAD in hypertensive patients. Subgroup analysis was stratified by age, cardiovascular disease, dyslipidemia, diabetes, smoking, and physical activity. Results After adjusting for confounding factors, decreased risk of PAD was observed in hypertensive patients with dietary fiber intake > 21 g [odds ratio (OR) = 0.67, 95% confidence interval (CI) 0.46-0.99]. Compared with people with dietary fiber intake ≤ 21 g, those with dietary fiber intake > 21 g were associated with decreased risk of PAD in hypertensive patients < 60 years (OR = 0.23, 95%CI 0.08-0.66). In hypertensive patients without dyslipidemia, dietary fiber intake > 21 g were associated with reduced risk of PAD (OR = 0.33, 95%CI 0.12-0.95). Decreased risk of PAD was also found in hypertensive patients without diabetes in dietary fiber intake > 21 g group (OR = 0.50, 95%CI 0.31-0.78). Dietary fiber intake > 21 g was linked with reduced risk of PAD in hypertensive patients in never smoke group (OR = 0.46, 95%CI 0.24-0.86). Conclusion Higher dietary fiber intake was associated with reduced risk of PAD in hypertensive patients, suggesting the importance of increase the daily dietary quality especially fiber intake in hypertensive people.